The Federal Democratic Republic of Ethiopia : 2004 Article IV Consultation and Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Statement; and Public Information Notice and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2005)
This paper examines Ethiopia's 2004 Article IV Consultation and Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). The PRGF program remains on track. All the quantitative performance criteria under the PRGF for end-March 2004, the structural performance criteria for end-June 2004, as well as all the benchmarks for these test dates have been met. In particular, the implementation of the Commercial Bank of Ethiopia (CBE) restructuring plan has progressed as planned. The 2004/05 federal budget requires substantial domestic financing as spending initiatives outpace revenue growth.